Mothers’ Knowledge of Kangaroo Mother Care for Premature Infants and Related Factors - Van Dem, Pham; Anh Tuan, Ta; Kim Loan, Ha; Thanh Nam, Nguyen; Tien Dung, Nguyen (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 37 No 2, 2021)
This study aims to describe premature infants’ mothers’ knowledge of kangaroo mother care (KMC) and related factors to identify methods for improving maternal and child health programs. This descriptive cross-sectional research was carried out at Bach Mai Hospital from October 2019 to March 2020 to interview 60 mothers with premature babies on KMC and some related factors. The research results show that 94.8% of the interviewed mothers were aware of KMC’s necessity; 91,78% of them knew about KMC, of which, only 8.3% without prior knowledge of KMC. In terms of sources of knowledge, 58.2% of the mothers learned about KMC from relatives or friends; via the Internet - 45.5% and 18.2% through health workers. The number of mothers -university graduates having prior knowledge about KMC was with p <0.05. The study recommends promotion of mothers’ education on the role and effect of KMC for premature infants, especially among those with a modest education level. Keywords Kangaroo mother care, preterm delivery, premature infants. References [1] R. Dawar, S. Nangia, A. Thukral et al., Factors Impacting Practice of Home Kangaroo Mother Care with Low Birth Weight Infants Following Hospital Discharge, J Trop Pediatr, Vol. 65, No. 6, 2019, pp. 561-566, https://doi.org/10.1093/tropej/fmz007. [2] A. C. Agudelo, J. L. D. Rossello, Kangaroo Mother Care to Reduce Morbidity and Mortality in Low Birthweight Infants, Cochrane Database Syst Rev, No. 8, 2016, pp. 111-116, https://doi: 10.1002/14651858.CD002771. [3] Y. Takubo, T. Nemoto, Y. Obata et al., Effectiveness of Kangaroo Care for a Patient with Postpartum Depression and Comorbid Mother-Infant Bonding Disorder, Vol. 2019, 2019, pp. 1-6, https://doi.org/10.1155/2019/9157214. [4] E. Akbari, N. B. Erez, M. Rodrigues et al., Kangaroo Mother Care and Infant Biopsychosocial Outcomes in The First Year: A Meta-Analysis, Early Hum Dev, Vol. 25, No. 122, 2018, pp. 22-31, https://doi.org/10.1016/j.earlhumdev.2018.05.004. [5] N. T. Nam, N. T. Dung, D. T. Anh et al., Characteristis Structure of Diseases in Neonatal at Pediatric of Department of Bachmai Hospital, Bachmai Clinical Jounral, Vol. 112, 2019, pp. 28-37 (in Vietnamese). [6] D. Kommers, M. Broeren, G. Oei et al, Oxytocin Levels in the Saliva of Preterm Infant Twins During Kangaroo care, Biol Psychol, Vol. 137, 2018, pp. 18-23. https://doi.org/10.1016/j.biopsycho.2018.06.009. [7] R. B. Garcia, A. Spilker, D. Goyal, Skin to Skin Contact: Newborn Temperature Stability in the Operating Room, MCN Am J Matern Child Nurs, Vol. 43, No. 3, 2018, pp. 158-163, https://doi.org/10.1097/NMC.0000000000000430. [8] F. Cavallin, G. Segafredo, D. Pizzol et al, Thermal Effect of a Woolen Cap in Low Birth Weight Infants During Kangaroo Care, Pediatrics, Vol. 141, No. 6, 2018, pp. 156-159, https://doi.org/ 10.1542/peds.2017-3073. [9] M. Evereklian, B. Posmontier, The Impact of Kangaroo Care on Premature Infant Weight Gain, J Pediatr Nurs, Vol. 34, 2017, pp. 10-16, https://doi.org/ 10.1016/j.pedn.2017.02.006.